Pemedal Agung at the Kertha Gosa Site, Klungkung, Bali (A Study of the Shape of the Statue) - I Putu Putra Suryadana; I Wayan Mudra (Journal of Aesthetics, Creativity and Art Management, 2023)
Pemedal Agung is one of the historic buildings located on the Kertha Gosa site, founded by the founder of power and the first throne holder of the Klungkung kingdom in Semarapura, namely Ida I Dewa Agung Jambe. The identity of Pemedal Agung has very unique forms of statues and ornaments. The uniqueness of the statues in Pemedal Agung can be seen from the use of ideas which certainly have their own uniqueness from the use of the idea of placing statues as ornaments or decorative elements in traditional architecture in Bali in general. The existence of the statues at the Kertha Gosa site, especially at the foot of Pemedal Agung, is not known specifically regarding the form of its embodiment, so this study is considered important to answer the proposed phenomenon. The purpose of this study was to find out the shape of the statues on the foot of Pemedal Agung at the Kertha Gosa Klungkung site. This study uses a qualitative descriptive approach, with data collection methods, namely observation and documentation. Data collection will be carried out in 2023 at the Kertha Gosa Klungkung Bali site, as the whereabouts of the research subject. The results of the study show that the shape of the statues found at the foot of Pemedal Agung at the Kertha Gosa site is one of the decorative elements of architectural heritage from the royal era in Bali. Researchers hope that this study can provide an overview in the form of science related to the existence of statues at the foot of Pemedal Agung at the Kertha Gosa site which is a decorative element of architectural heritage from the royal era in Klungkung.